Analisis Dampak Perubahan Tata Guna Lahan terhadap Debit Limpasan di Kecamatan Selaparang dan Mataram - Budianto, Muh Bagus; Sulistiyono, Heri; Setiawan, Ery; Hartana, Hartana; Zainudin, Rahman (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2024)
Selaparang and Mataram Districts are two of the six districts in the Mataram City area that experience changes in land use every year. This change can affect the absorption capacity of groundwater in the area to decrease so that if there is rain with a fairly high intensity, it can cause water to overflow to the surface and inundate the area. This study was conducted to determine the runoff discharge that occurred due to changes in land use that occurred in 2013, 2018, and 2023, and to compare the runoff discharge in 2023 with the runoff discharge based on the Regional Spatial Plan of Selaparang and Mataram Districts in 2011-2031. The initial stage in this study was to collect several secondary data such as rainfall data, land use based on the regional spatial plan, and others that can be obtained from related agencies. After that, the next stage is the delineation of the catchment area and land use analysis with the help of ArcGis and Google Earth software, as well as runoff discharge analysis. The results of the analysis show that the percentage increase in runoff discharge that occurred in Selaparang District in 2013-2018, 2018-2023, and 2013-2023 was 2.21%, 1.40%, and 3.64%, respectively. Meanwhile, the percentage increase in runoff discharge in Mataram District in 2013-2018, 2018-2023, and 2013-2023 was 2.43%, 0.73%, and 3.18%, respectively. Based on this, it can be concluded that the reduction in green land area and the increase in built-up land area each year will cause an increase in the runoff coefficient value, so that the runoff discharge that occurs in Selaparang and Mataram Districts also increases every year.